THE UNIQUENESS OF SHUKUR KHOLMIRZAYEV’S STORIES AND THE CHARACTERS IN THEM - Mohinur Khairullayeva Golib kizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: Shukur Kholmirzayev is considered one of the creators with a unique style in the Uzbek literature of the 20th century. Shukur Kholmirzayev entered Uzbek literature in the 60s. He won the hearts of students with his first stories. The stories he created caught the attention of Abdulla Qahhor. Later, he started writing novels. Shukur Kholmirzayev paid special attention to the characters in his stories. He tried to reflect them in a sincere and natural way. In the stories he created, the image of a child was especially important.